Pāratiyiṉ pulamainalam : karuttaraṅkak kaṭṭuraikkōvai - Vaḷaṉ Aracu, Pā., 1940- (Katiravaṉ Patippakam, 1982)
Papers presented at a seminar, organized by the Tirunelvēlit Taṉit Tamiḻ Ilakkiyak Kaḻakam, Tamil literary organization, on the life and works of Pāratiyār, 1882-1921, Tamil litterateur and Indian freedom fighter.